Interlocking Firm Networks in the German Knowledge Economy. On Local Networks and Global Connectivity - Lüthi, Stefan; Thierstein, Alain; Bentlage, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
the knowledge economy is a key driver of spatial development in metropolitan regions. a relational perspec- tive on its business activities emphasizes the importance of knowledge-intensive firms and their networking strategies. the aim of this paper is to analyse the spatial networking patterns created by the interaction of knowledge-intensive firms and to place these activities in the theoretical context of the knowledge economy. Our central question is which large-scale interlocking networks and functional urban hi- erarchies are produced by advanced Producer services and High-Tech firms located in Germany. The intra-firm loca- tional networks of these companies are analysed on three spatial scales: global, national and regional. the empirical findings show that the functional urban hierarchy in the german city system proves to be steeper than is claimed by the political debate on german Mega-city regions.